An investigation of the corporate planning concept in a South African motor manufacturing undertaking - Coman, Keith Rawson (Rhodes University, Faculty of Commerce, Department of Economics, 2026)
The intention of this dissertation is to attempt to project the theoretical concept of Corporate (or Long-Range) Planning into the reality of one of South Africa's major motor vehicle manufacturing company's task environment. It is a sad fact that there are no universally - applicable practical planning "laws" (as are present within the discipline of, say, Physics) amidst the ever-changing hurly-burly world of modern commerce and industry. Accordingly, there are very real distinctions between distilled Corporate Planning theory, as it is propounded in the many available books and articles, and Corporate Planning practice as actually implemented. This is true largely by virtue of the fact that in the same way as persons differ in their physical and mental make-up, so too do individual companies
Keywords: Business planning -- South Africa; Motor vehicle industry -- South Africa